Low abundance of long-tongued pollinators leads to pollen limitation in four specialized hawkmoth-pollinated plants in the Atlantic Rain forest, Brazil - Amorim, Felipe Wanderley [UNESP]; Wyatt, Graham E.; Sazima, Marlies (Springer, 2014)
Long-tubed hawkmoth-pollinated species present some of the most remarkable examples of floral specialization depending exclusively on long-tongued hawkmoths for sexual reproduction. Nonetheless, long-tongued hawkmoths do not rely exclusively on specialized plants as nectar sources, which may limit sexual reproduction through pollen limitation. However, very few studies have quantified the level of pollen limitation in plants with highly specialized floral traits in tropical regions. In this context, we studied four sympatric hawkmoth-pollinated species in a highland Atlantic Rain forest and assessed pollen limitation and their dependence on pollinators by analyzing the floral biology, breeding system, pollination mechanisms, and abundance of long-tongued pollinators. We showed that the four species are self-compatible, but are completely dependent on long-tongued hawkmoths to set fruits, and that flower visitation was infrequent in all plant species. Pollen limitation indices ranged from 0.53 to 0.96 showing that fruit set is highly limited by pollen receipt. Long-tongued moths are much less abundant and comprise only one sixth of the hawkmoth fauna. Pollen analyses of 578 sampled moths revealed that hawkmoths visited ca. 80 plant species in the community, but only two of the four species studied. Visited plants included a long-tubed hawkmoth-pollinated species endemic to the lowland forest ca. 15-20 km away from the study site. Specialization index (H (2) ' = 0.20) showed that community-level interactions between hawkmoths and plants are generalized. We suggest that sexual reproduction of these highly specialized hawkmoth-pollinated species is impaired by competition among plants for pollinators, in conjunction with the low abundance and diversity of long-tongued pollinators.
Keywords: Habenaria johannensis; Habenaria paulistana; Hillia parasitica; Nectar sugar gradient; Pollen limitation index; Posoqueria latifolia